THE RELATIONSHIP BALANCE AND ARM MUSCLE STRENGTH TO SHOOT LAY-UP SKILLS IN BASKETBALL - Ommedi Saputra; Syafaruddin Syafaruddin; Achmad Richard Victorian (Universitas Negeri Medan, 2023)
This study aims to analyze the relationship between balance and arm muscle strength on lay-up shoot skills in basketball games for MA extracurricular students. Riyadus Sholihin. The sample in this study was taken as a whole or total sampling, namely 30 students. The balance test uses the stand stroke test, for arm muscle strength uses the flexed-arm hang test and for lay up shoots uses the lay up shoot ability test. The data analysis technique was processed with proportions and the hypothesis was tested using correlation with the help of a computer in the excel and SPSS 23 programs. Based on the analysis of the proportion of the data obtained, namely for the results of the balance, the proportion of 100% was obtained, totaling 30 students who had an average balance result in the less category for girls and medium category for boys. The results of arm muscle strength have an average category of less than once for women and very few categories for men. Whereas the results of the ability to lay up shoot have an average result with a less category for women and an adequate category for men. This means that there is a contribution to the relationship between balance and arm muscle strength on lay-up shoot skills in basketball games.